PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays sacaratha Sturt. L) PADA BERBAGAI JARAK TANAM DAN WAKTU OLAH TANAH - Silaban, Evy Thyrida; Purba, Edison; Ginting, Jasmani (Universitas Sumatera Utara, 2013)
The aim of the research was to evaluate the growth and production of sweet corn (Zea mayssacharata Sturt. L) planted at various distance and land preparation (soil tillage prior to planting).The treatments were arranged in split plot design with three replication. The study consists of twofactors, as main plot was time of soil tillage prior to planting (one and seven days) whereas sub plotwas planting distance consist of four different spaces : 70cm x 10cm, 70cm x 20cm,70cm x 30cm dan 70cm x 40cm. Result showed that the plant spacing consists of 70cm x40cm performs significant effect on number of leaves, stem diameter, cob diameter, and productionper plant, but not significant effect on flowering time and number of cobs per plot. The interactionbetween time of planting and planting space had no significant effect on plant height, number ofleaves, stem diameter, days to flowering, cob diameter, number of cobs per plot, weight of cobs perplot and production per plant.Keywords: sweet corn, plant spacing and tillage time